HUBUNGAN BERPACARAN DENGAN PRESTASI AKADEMIK SISWA SMK KESEHATAN WIRAHUSADA MEDAN - Renta Megasari Situmorang; Afnijar Wahyu (Jurnal Riset Multidisiplin Edukasi, 2025)
Dating relationship or often referred to as dating, is a verbal expression that indicates falling in love or getting to know someone. Dating can have both positive and negative impacts on students' academic achievement at school. The lack of role of dating relationships is considered to influence the improvement of academic achievement. The purpose of this study was to explore the relationship between dating and academic achievement of Medan Health Vocational School students. The method in this study used a quantitative method with a cross-sectional approach. The sample size selected using the Total sampling technique was 43 respondents. The relationship between variables was analyzed using the Spearman statistical test. The results of the study showed that there was a significant relationship between dating status and academic achievement with a p-value of 0.000 indicating a fairly strong positive correlation. It is recommended for further researchers to add variables such as parenting patterns, peer influence, maturity level in dating, the influence of health and knowledge.